Urban Poverty Dynamics And Its Determinants: Evidence From Household-Level Logistic Models In Aceh And Bengkulu, Indonesia - Ekaputri, Retno Agustina; Yefriza, Yefriza; Barika, Barika (Universitas Bengkulu, 2025)
Abstract Aceh and Bengkulu are among the provinces in Sumatra with relatively high poverty rates, although both have shown gradual declines in recent years. In Aceh, the poverty rate decreased from 14.64% in 2022 to 14.23% in 2024, while in Bengkulu it declined from 14.62% to 13.56% over the same period. Urban poverty remains consistently lower than rural poverty; however, disparities in urbanization patterns between the two provinces suggest potential differences in the determinants of urban household poverty. Aceh is characterized by more developed urban centers such as Banda Aceh and Lhokseumawe, whereas Bengkulu is dominated by smaller urban areas. This study aims to analyze the determinants of urban household poverty and compare their characteristics across selected cities in Aceh (Sabang, Banda Aceh, Lhokseumawe, Langsa, and Subulussalam) and Bengkulu City. An explanatory research design is employed using secondary data. The analysis combines descriptive statistics, logistic regression, and comparative testing. The results indicate that in urban Aceh, housing floor area, household size, and participation in the basic food assistance program significantly influence poverty status. In contrast, sanitation conditions and participation in the Family Hope Program (PKH) are significant determinants in urban Bengkulu. Furthermore, the comparative analysis reveals no statistically significant differences in urban poverty between the two provinces. These findings highlight that, despite similar poverty levels, the underlying determinants vary across regions, implying the need for region-specific policy interventions to effectively address urban poverty. Keywords : Urban Poverty, Multidimensional Poverty, Logistic Regression, Regional Comparison Abstrak Provinsi Aceh dan provinsi Bengkulu merupakan daerah dengan persentase penduduk miskin tinggi di pulau Sumatera. Di provinsi Aceh sebesar 14,64 di tahun 2022 turun menjadi 14,23 persen pada tahun 2024. Adapun di provinsi Bengkulu sebesar 14,62 turun menjadi 13,56 persen pada tahun 2024. Ditinjau dari proporsi kemiskinan perkotaan dan perdesaan, umumnya kemiskinan di wilayah perkotaan lebih rendah daripada kemiskinan perdesaan. Kedua provinsi ini memiliki tingkat urbanisasi yang berbeda, di mana Aceh memiliki kota-kota besar seperti Banda Aceh dan Lhokseumawe, sedangkan Bengkulu lebih didominasi oleh kota kecil seperti Bengkulu. Provinsi Aceh dan Bengkulu, misalnya, memiliki karakteristik sosio-ekonomi yang berbeda, sehingga menarik untuk dikaji lebih dalam mengenai faktor-faktor yang mempengaruhi kemiskinan rumah tangga di perkotaan di kedua provinsi tersebut. Desain penelitian ini adalah penelitian eksplanatori. Pertama penelitian ini akan menganalisa karakteristik rumah tangga miskin di Kota Sabang, kota Banda aceh, kota Lhokseumawe, kota Langsa, kota Subulussalam, dan kota Bengkulu. Penelitian ini menggunakan metode analisis deskriptif, regresi logistik, dan analisis komparatif. Hasil penelitian menemukan bahwa berdasarkan variabel Luas lantai, jumlah anggota keluarga, dan program sembako berpengaruh signifikan terhadap kemiskinan di perkotaan Aceh, sedangkan sanitasi dan PKH berpengaruh di perkotaan Bengkulu. Uji komparatif menunjukkan bahwa secara statistic tidak terdapat perbedaan antara kemiskinan antara perkotaan provinsi Aceh dan Bengkulu. Kata kunci : Kemiskinan, Perkotaan, Multidimensi, Regresi Logistik